Potential health risk estimation of naturally occurring radionuclides intake due to the consumption of seafood around Coastal zone - Kumar Pandion; Kantha Deivi Arunachalam (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2022)
As part of a regional baseline study, the distribution of naturally occurring radioactive materials in the marine fish diversity consumed by different age group representatives living in the Kalpakkam coastal zone was studied. The average activity of natural radionuclide in 238U, 232Th, and 40K (n = 40) was 28.51, 239.58, and 118.95 Bq kg-1, respectively. The annual dose of ingestion, lifetime carcinogenic risk assessment and cancer risk assessment due to 238U, 232Th, and 40K were estimated by marine fish diversity in children aged 1-4,5-9,10-14,15-17 years, adults, pregnant women, and the fishing community. The Hospital-Based Cancer Registry (HBCR) compares to the coastal zone. Statistical studies such as Pearson correlation analysis, Principle component analysis, and Cluster analysis report check that the current levels of natural radionuclide do not pose a significant radioactivity threat to the residents based on the activity of the radionuclide.